2018
DOI: 10.1142/s0219887818500652
|View full text |Cite
|
Sign up to set email alerts
|

Four-qubit systems and dyonic black Hole–Black branes in superstring theory

Abstract: Using dyonic solutions in the type IIA superstring theory on Calabi-Yau manifolds, we reconsider the study of black objects and quantum information theory using string/string duality in six dimensions. Concretely, we relate four-qubits with a stringy quaternionic moduli space of type IIA compactification associated with a dyonic black solution formed by black holes (BH) and black 2-branes (B2B) carrying 8 electric charges and 8 magnetic charges. This connection is made by associating the cohomology classes of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In this section, we reconsider the study of dyonic solutions in type II superstrings compactified on n-dimensional real manifolds X n . It has been remarked that each compact manifold possesses some geometric information which can play a crucial role in the determination of the superstring theory spectrum in 10 − n dimensions [22]. In particular, they can be exploited to produce all physical data in lower dimensional superstring models.…”
Section: Stringy Dyonic Black Objects In Arbitrary Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we reconsider the study of dyonic solutions in type II superstrings compactified on n-dimensional real manifolds X n . It has been remarked that each compact manifold possesses some geometric information which can play a crucial role in the determination of the superstring theory spectrum in 10 − n dimensions [22]. In particular, they can be exploited to produce all physical data in lower dimensional superstring models.…”
Section: Stringy Dyonic Black Objects In Arbitrary Dimensionsmentioning
confidence: 99%
“…Using string dualities between type IIA and heterotic superstrings, four-qubit systems in the context of type II superstring compactifications have been investigated [20,21]. It has been revealed that such qubit systems are related to a stringy moduli space SO(4,4) SO(4)×SO(4) considered as a reduction of the moduli space of six dimensional supergravity model obtained from the compactification of the heterotic superstring on T 4 [22]. Moreover, the string/string duality has been exploited to show that there exists an interplay between four-qubit states and a particular ordinary dyonic black hole in six dimensions having eight electric and eight magnetic charges.…”
Section: Introductionmentioning
confidence: 99%
“…Since then the four-qubit classification has generated a large amount of work including alternative perspectives on the classification itself [26,10,24,22,8], invariants-covariants approches of the classification [25,33,27], geometric intepretations [23,20,21,26] and connection with others domains in physics [5,6,4]. Hypergraph states are quantum states that generalize the notion of graph states where qubits composing the system are given by vertices and the interaction between the qubits/vertices are described by edges or hyperedges (See Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, works based on toric manifolds has been developed leading to a classification of qubit systems in terms of black hole charges in type II superstrings in the presence of D-brane objects [16]. Moreover, some studies have been proposed by using the Andinkra graph theory being exploited in the study of the supersymmetric representation theory [13,14,15,16,17]. In particular, these graphs have been elaborated to classify a class of qubits linked to extremal black branes in type II superstring compactified on complex manifolds [13].…”
Section: Introductionmentioning
confidence: 99%